Test Preparation in the Accountability Era: Toward a Learning‐Oriented Approach. Issue 1 (17th November 2016) - Gebril, Atta
Abstract : The article introduces a learning‐oriented approach to test preparation that could help in easing the tension between learning and assessment. The first part of the article discusses the different concepts that are usually used in the context of test preparation. The second section reports on the literature pertaining to the effects of test preparation on teaching, learning, and test performance. The article also attempts to differentiate between appropriate and unhealthy practices and show the intricate differences between these concepts. In conclusion, the author suggests a number of guidelines for different stakeholders about how to conduct test preparation activities effectively and how to avoid the common pitfalls when carrying out this task. These guidelines focus specifically on how to develop and carry out test preparation activities that are learning‐oriented, how to develop assessment tasks that discourage inappropriate test preparation practices, and how to use strategies for promoting professionally sound test preparation activities.